Wonderful Archipelago As The Result Of Culture Diaspora Through Carnavals In Indonesia - Lois Denissa; Yasraf Amir Piliang; Pribadi Widodo; Nuning Yanti Damayanti Adisasmito (Institut Seni Indonesia Denpasar, 2016)
The Fashion Carnaval, which is a phenomenon in district city of Jember, has been held every July to August since 2003. The existence ofthis event has a positive impact for the peopleliving in Jember. It does not only encourage the creativity of young people, but also improves the social life, economy, culture, politics and tourism of Jember.Jember Fashion Carnaval is in the process of becoming an iconic event of Jember, We knew this event from cross-border communication, mass media and its routine roadshow in the country and abroad, as well as its achievements in various international beauty contests, The successful Jember Fashion Carnaval (JFC) has made the city of Jember more internationally recognized and this has a positive impact on other cities in Indonesia in a way that this motivates those cities to create something interesting about them. The other regions are motivated to discover their local potency and make it in such a way that it can become a similar successful fashion carnaval. Indonesian people have been familiar with such art festival that is held on the streets and a part of ritual. This kind of activity has been a strongly rooted tradition since many years ago until now.Changing an art event into a contemporary performing art in the form ofa fashion carnaval is not something contrary to the culture of Indonesian society. Both have visual similarity and use the streets as their venues. Their purpose is the only difference. The Jember Fashion Carnaval, that has successfully become the icon of the city, has encouraged what is known as Wonderful Archipelago, a carnaval culture diaspora phenomenon, which is easily absorbed, spread and becomes fruitful across the countryKey Words: Culture Diaspora, Jember Fashion Carnaval, Wonderful Archipelago